Efektifitas Penerapan Metode Family Centered Care Terhadap Kepuasan Keluarga Pada Anak Dengan Hospitalisasi - Muhammad Nurlamsyah; Ike Nurjana Tamrin; Muhammad Asikin; I Takko Podding; Sukmawati Sukmawati (Media Kesehatan Politeknik Kesehatan Makassar, 2025)
Nursing care in the pediatric ward is measured based on parental satisfaction. Parental satisfaction is achieved when the child's needs for nursing care are met during hospitalization. If performance falls below expectations, customers will be dissatisfied, but if performance exceeds expectations, customers will feel satisfied or happy. To improve quality, one approach is to measure patient and family satisfaction with the implementation of Family-Centered Care in the hospital. Prioritizing patient and family satisfaction is a hallmark of high-quality healthcare services. The purpose of this study is to determine the effectiveness of the implementation of Family-Centered Care on family satisfaction for children hospitalized at RSU Andi Makkasau Parepare. This survey is a quantitative study using an analytical design with a cross-sectional approach. The sampling technique used is accidental sampling. The population of respondents was 60 respondents. The sample size was determined using the Slovin formula with a sample of 53 respondents. The instruments used were the Family-Centered Care questionnaire and the family satisfaction questionnaire using a Likert scale. Data analysis was performed using the Chi-Square Correlation statistical test and analyzed using statistical analysis. The results of the study found that there was an effect of the implementation of Family-Centered Care on family satisfaction in children hospitalized at RSU Andi Makkasau Parepare, with a significance level of p-value = 0.000 < 0.05. The conclusion of the study is that there is a significant effect between Family-Centered Care and the level of family satisfaction in children hospitalized at RSU Andi Makkasau Parepare. Therefore, it is hoped that nurses can maintain the implementation of Family-Centered Care to improve service and satisfaction through nursing care. Keywords: Children, Hospitalization, Family-Centered Care, Family Satisfaction